Heterogeneous mutations in the human lipoprotein lipase gene in patients with familial lipoprotein lipase deficiency. - Gotoda, T (1991)
The DNA sequences were determined for the lipoprotein lipase (LPL) gene from five unrelated Japanese patients with familial LPL deficiency. The results demonstrated that all five patients are homozygotes for distinct point mutations dispersed throughout the LPL gene. Patient 1 has a G-to-A transition at the first nucleotide of intron 2, which abolishes normal splicing. Patient 2 has a nonsense mutation in exon 3 (Tyr61----Stop) and patient 3 in exon 8 (Trp382----Stop). The latter mutation emphasizes the importance of the carboxy-terminal portion of the enzyme in the expression of LPL activity. Missense mutations were identified in patient 4 (Asp204----Glu) and patient 5 (Arg243----His) in the strictly conserved amino acids. Expression study of both mutant genes in COS-1 cells produced inactive enzymes, establishing the functional significance of the two mis-sense mutations. In these patients, postheparin plasma LPL mass was either virtually absent (patients 1 and 2) or significantly decreased (patients 3-5). To detect these mutations more easily, we developed a rapid diagnostic test for each mutation. We also determined the DNA haplotypes for patients and confirmed the occurrence of multiple mutations on the chromosomes with an identical haplotype. These results demonstrate that familial LPL deficiency is a heterogeneous genetic disease caused by a wide variety of gene mutations.